From history of Electrical Engineering III: Electromagnetism discovery and its fundamental laws in the first half of 19-th century - Mikerov, Alexander G. (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
This paper contains an overview of main findings in electromagnetism started from the Oersted's observation including contributions of A. M. Ampere, M. Faraday, J. Henry, E. Lenz, W. Weber, W. Sturgeon and also fundamental papers of G. Ohm and G. Kirchhoff in theory of electrical networks. All this resulted in the classical Maxwell's electrodynamics background creation.